Norms of Etiquette Communication in Foreign Language Teaching (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article investigates various norms of etiquette communication. The phatic function of the language is examined, aimed at establishment and mutual support of the contact in communication process. It is specified that speech etiquette is used for support of the contact among people, i.e. it is the major factor of the phatic communication. In this aspect a human is a product and a result of communication with other people, i.e. as intersubjective creature of language in speech etiquette.
Keywords: etiquette communication; language; speech etiquette; phatic communication; communication